STORY TELLING SEBAGAI STRATEGI PEMBELAJARAN MORAL ANAK USIA 4-6 TAHUN: ANALISIS BLIBLIOMETRIK (2009-2023) - Adelia Rahma; Ira Zafirah; Nur Alpita; Revina Julia; Zulfatul Kiromiyah; RR. Deni Widjayatri (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2024)
This research aims to find out data related to the effectiveness of Story Telling as a Learning Strategy for Children aged 4-6 years. The method used is through a bibliometric review of the Google Scholar database between 2009 and 2023 with the results of 905 data selected to 550 data. The publish or perish software was utilized as data reception. Meanwhile, the Vos Viewer application was used to analyze the data. This analysis produces data related to the cultivation of moral values in children aged 4-6 years through the story telling method. Contribute to the discourse of early childhood education and serve as a resource for educators, parents, and caregivers that is innovative and effective for moral development in early childhood. Analyze this data to show that the story telling method has an impact on the moral values of early childhood.